The use of extruded feed in fish food - Pezzato, L. E. (Technomic Publ Co Inc, 1999)
In our country, the intensive culture of fish has been making progress due to the availability of extruded rations, which are characterized by the way they have been formulated to assist the nutritional demands of the tropical species and for facilitating a better practice of alimentary handling. This process checks the extruded product density and the desirable physical/chemical aspects to a diet that should be handled in the water, the critical factor of this activity. It is important to emphasize that this product stays to the surface of the water, facilitates the consumption control and the observation of the general aspects of the school of fish, as well as guaranteeing that no deterioration of the physical/chemical characteristics of the water occurs. The floating characteristic of the extruded ration is preferable for farmers because most of the tropical species feed at the surface of the water. In some cases, in the function of the alimentary habit, the thermal conditions of the water and the handling system produce granules with different densities. This is due to the humidity and the applied cooking heat, which modifies the time of hydration, and consequently the ability to float. To establish the physical presentation idea for a ration for tropical fishes, it is necessary that the pellets come in sizes, textures, humidities and densities in order to allow for the different phases of the lives of the fishes. This ration should be the result of characteristics of the species, such as the anatomophysiologics particularities, alimentary habits, digestive capacity and alimentary behavior. Only in this way is it possible to offer to those fishes a ration whose nutritious value and physical presentation facilitate the best biological and economic answers.Those aspects need to be reviewed because the tropical species that are cultivated in our country present selective behavior in relation to the size of the pellet. Generally, this has access to the digestive system without waste; the digestibility, therefore, is dependent upon the size of the particles and the physical aspects of the pellets. They should still consider that those granules could be less abrasive and softer. The extruded rations available in the national market present a qualitative reference to its proteic level, whose consequence allows us to infer that those are overestimated for the final phase of those fishes. Thus, the final cost of production is made unfeasible. In this point of view of the development of the national fish culture, and the growing adoption of the intensive system of production, it can link that such progress is a function of the availability of the rations in the extruded form. Although this technique of processing of rations has revolutionized the market in such a way that has been seen as preferable for farmers, some feel that there is a lack of products best suited for the initial phases of fingerlings production.